Culture and imperialism - Said, Edward W (New York Vintage Books, 1994)
A landmark work from the intellectually auspicious author of Orientalism that explores the long-overlooked connections between the Western imperial endeavor and the culture that both reflected and reinforced it. "Said is a brilliant . . . scholar, aesthete and political activist."--Washington Post Book World.
Originally published: New York : Knopf, 1993.
Keywords: European literature -History and criticism -Theory, etc